Some notes on the method of the economy and the method of economic research - Rivas Santos, Pablo Hermenegildo (2019)
This article qualitatively analyzes the Method that Economics uses (Human science dedicated to the study of universal laws that regulate Human Action in a world where scarcity of resources and infinite human needs prevails) to solve the economic problems that interest it. the society ; and on the other hand it qualitatively analyzes the Method that the economy uses to carry out economic research.